Defence heritage as a cultural heritage tourism resource: Case of cyprus - Mısırlısoy, Damla; Günçe, Ka?an (International Information and Engineering Technology Association, 2021)
Cyprus has one of the richest histories of Europe and the Middle East. As the result of being an island and having a strategic location, Cyprus had been occupied by different civilizations throughout history. Since the island faced many attacks throughout history, different buildings and structures were built to defend the island from its enemies. Defence heritage should be identified, documented and conserved since they are important part of the collective memory of the island. The only way to sustain these monuments is to reuse with an appropriate function since they have already lost their original function. The purpose of the study is to highlight the significance of defence heritage of the island and propose reuse strategies as a cultural tourism resource. The method of the study to includes literature surveys and observations through site survey. These data are used for developing reuse strategies by considering defence heritage as a cultural heritage tourism resource. Defence heritage structures can be used as tool for contributing cultural tourism of the island. Defence heritage is an important part of cultural heritage; therefore, they should be transferred for further generations through conservation and reuse. © 2021 WITPress. All rights reserved.
Keywords: Adaptive reuse; Conservation; Cultural heritage; Cultural heritage tourism; Cyprus; Defence heritage